2002
DOI: 10.1007/s00406-002-0383-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between negative symptoms and peripheral G protein levels in mononuclear leukocytes of deficit and nondeficit schizophrenics

Abstract: Receptor-coupled G proteins were measured in mononuclear leukocytes (MNL) of 17 drug-treated patients with deficit schizophrenia (DS) and 16 drug-treated patients with nondeficit schizophrenia (NDS). No significant difference was found in MNL levels of G(alphas), G(alphai), G(alphaq) and G(beta) proteins between the two groups; however, MNL levels of G(alphas) were inversely correlated to the severity of negative symptoms in DS patients, while MNL levels of G(alphaq) were positively correlated to negative symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It is notable that previous work investigating deficit and non-deficit patients for peripheral G protein levels found a significant relationship between these assays and degree of negative symptoms in both groups of patients (Monteleone et al 2002). We speculate that the difference in PTC tasting status reflects underlying G protein-coupled signal transduction abnormalities that have some contribution to the clinical symptoms of the illness.…”
Section: Discussionmentioning
confidence: 68%
“…It is notable that previous work investigating deficit and non-deficit patients for peripheral G protein levels found a significant relationship between these assays and degree of negative symptoms in both groups of patients (Monteleone et al 2002). We speculate that the difference in PTC tasting status reflects underlying G protein-coupled signal transduction abnormalities that have some contribution to the clinical symptoms of the illness.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, we observed the lack of association between WM performance in SZ patients with positive and general symptoms as well as apathy in the presence of a correlation with negative symptoms. These findings may be attributed to the fact that while negative symptomatology is believed to result from decreased dopaminergic activity in the prefrontal cortex directly involved in WM (Okubo et al, 1997 ; Heckers et al, 1999 ; Monteleone et al, 2002 ). Positive and general symptoms as well as apathy are associated with possibly altered activity in the areas less crucial to WM performance, such as the hippocampus (Krieckhaus et al, 1992 ; Tamminga et al, 2010 ) and the basal ganglia (Pankow et al, 2012 ; Khadka et al, 2013 ; Sorg et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although nontaster status has been linked to a variety of medical disorders, there have been few investigations of PTC taster status in schizophrenia (6)(7)(8). Abnormalities in the function and/or expression of G protein signaling pathways have been reported in patients with schizophrenia and appear to be implicated in prepulse inhibition of the startle reflex and negative symptoms (9,10). Therefore, we anticipated that patients would show a differential pattern of PTC tasting status relative to healthy comparison subjects and that a similar pattern would be observed in their non-ill firstdegree relatives.…”
mentioning
confidence: 98%